Using Constructivism to explore students’ perspectives on learning Mandarin Lexical - Lee, Hui Ling; Shaari, Jamilah; Che Abas, Atirah Izzah; Abdul Ghani, Kamarulzaman (UMK Press, 2019)
Teaching lexical items plays an important role in second or foreign language classroom. There has been a dramatic increase in studies done on the importance of adopting the right methods to introduce the students with lexical items considering the central role that lexis plays in any languages. The purpose of this study is to investigate the students’ perspective on the Constructivist Learning Theory in learning Mandarin lexical more effectively. Nine types of teaching methods introduced in this study are: (1) compare and contrast, (2) word wall, (3) note taking and summarising, (4) recitation, (5) cues, question and activating prior knowledge, (6) role play, (7) non-linguistic representation, (8) homework and practice, and (9) analysis of students' work and discussion. Descriptive survey method which involves questionnaires was employed and 35 participants were selected for this study. The findings revealed that the students perceived note taking and summarising as well as homework and practice as the most helpful methods for learners to minimize the negative transfer of their mother tongue in Mandarin lexis learning. They also mentioned that note taking and summarising were the most interesting methods as compared to other methods whereas homework and practice was most effective for them. It is recommended that foreign language instructors in Malaysian higher education institution to keep updated on the current approach in introducing lexical items in an effective and interesting manner.